INDIVIDUAL SPORT RESULTS AND STOCK RETURNS - Jokinen, Rami (My University, 2011)
Behavioral finance studies have examined the link between behavioral biases and asset prices and one of those bases is shown to be investor’s mood. Many studies have shown that there is a link between investor’s mood and stock returns. The objective of this thesis is to expand the existing evidence linking mood to stock returns and to examine the stock market reaction to sudden changes in investor’s mood. Psychological studies have pointed out that sport results have an effect on people’s mood and via that their investment behavior. The purpose of this thesis is to study is there a link between individual sport results, investor’s mood and stock returns. There have been earlier studies that have showed that team sport results have an impact on investor’s mood. This thesis investigates if the same link can be found between individual sport results and stock returns. Therefore, the results from Olympic Games are used, which may have some interesting properties as a measurement of mood. The data used in this thesis consist of the price of Nasdaq OMX Helsinki all share index. The time-series data for regression are formed by closing price of the index, which returns are defined logarithmically. Nasdaq OMX Helsinki all share index form a time series between 5.1.1987-19.3.2010. Failures and successes from Olympic Games are used to measure sudden changes in investor’s mood and also 3 formula 1 championship titles are included in the sample data. To estimate the effect of failures and successes on stock returns, a regression model is used. No negative stock market reaction after failure is found. No evidence of positive stock market reaction after success is found, except after gold medal. It can be concluded that only gold medal have an impact on stock returns when examining the link between individual sport results and stock returns. Other success or failures have no impact on stock returns. The results suggest that the effect associated with failure or success in Olympic Games is too small to influence national stock market index, except gold medals.
Keywords: Behavioral Finance; Investor Sentiment; Stock Returns; Sport; Olympic Games; Individual Sport Results; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Master's Degree Programme in Finance|